Extraction of Betacyanin from Hylocereus Polyrhizus Peel Effect of Operating Conditions - Azimah, Saman; Mimi Sakinah, A. M.; Zularisam, A. W. (2016)
Betacyanin pigment is a red purple colour that can be produced from the peels of Hylocereus polyrhizus fruit. The peel of Hylocereus Polyrhizus is often regarded as a waste hence this study was aimed to investigate the feasibility of using the peel as a natural dye source. Betacyanin extraction was studied from this by-product using solvent extraction method in order to identify the preliminary parameters range for different factors. In this research, the influence of extraction time, solvent ratio, and solid loading ratio towards the total betacyanin content was studied. The analysis of the total betacyanin content was conducted by means of the absorbance measurement using the UV-Vis Spectrophotometer. The best parameter range for further study was between extraction time 120 – 180 min, ethanol percentage at 20 – 60 % and liquid to solid ratio (LSR) loading ratio 4 to 8 v/w in order to obtain highest betacyanin content from Hylocereus polyrhizus peel.